Catalyst freesingle-stepfabricationofSnO2/ZnO core–shell nanostructures - Thanihaichelvan, T.; Haseeb, A.S.M.A.; Akbar, S.A.; Sabri, M.F.M. (Elsevier, 2013)
Facile catalyst-freesynthesisofSnO2/ZnO core–shell nanowiresandhierarchicalnanostructuresgrownviaaone-stepcarbonassistedthermal evaporation methodunderambientpressureisreported.Awhitewool-likemassformsatthesideandontopofaquartzboatduringtheprocess that wasanalyzedby field emissionscanningelectronmicroscopy(FESEM).X-raydiffractionpatternsexhibitthattheas-synthesizedSnO2/ZnO nanostructures consistofsinglephaseofZnOandSnO2. Transmissionelectronmicroscopy(TEM)suggeststhatthewool-likemasscontains core–shell typeSnO2/ZnO nanowiresaswellashierarchicalnanostructures.Inthecore–shell nanowires,SnO2 forms thecore,whileZnOisthe shell. Inthehierarchicalnanostructures,hexagonalshapedZnObranchesgrowontheZnOshelllayeratlonggrowthduration.Bothtypesof nanostructures formedinthequartzboataresuggestedtogrowbythevapor–solid (VS)mechanism.Structuralcharacteristicsofthe nanostructures arediscussed.Thesenanostructuresmayhavepotentialapplicationsinchemicalgassensorsandphotovoltaicdevices.
Keywords: Electronmicroscopy; Hierarchicalnanostructures